Identification and screening on prevalency of bacteria in wastewater of batik industry - Jamali Sukaimi (2013)
Despite generating giant income for Malaysia, the batik industry has produced high amount of wastewater containing dyes and other pollutants which tremendously polluted the environment and endangers the living things. By understanding all the consequences and its effects, a solution must be implemented to utilize bacteria as agents to treat the wastewater. The identification on the bacteria that able to degrade the pollutant was carried out by Biochemical test following Bergey's Manual of Determinative Bacteriology. Then, each of the bacterium was screened based on its pre-valence. The bacteria also were tested on its effectiveness in removing the color. Besides that, water quality of each sampling site was also tested. All the water quality parameters showed the results that under permitted level regulated by Environmental Quality (Industry Effluents) 2009. There were five bacteria identified that able to degrade the dyes which are Staphylococcus auriens, Micrococcus luteus, Micrococcus varians, Streptococcus spp and Enterococcus Micrococcus luteus spp performed the best ability in degrading the dyes. It can degrade the RY-84 up to 52.31 %. The Staphylococcus auriens screened as the most dominant bacteria found in all sampling site except for Site 1. RY-84 is the most easily degraded by the bacteria. It can be degraded up to 52.31%. This approach is not only easy, economy but it also very efficient.